Correction: Triethylamine-methanol mediated selective removal of oxophenylacetyl ester in saccharides. Issue 12 (11th March 2022) - Rasool, Javeed Ur; Kumar, Atul; Ali, Asif; Naveed Ahmed, Qazi
Abstract : Correction for 'Triethylamine-methanol mediated selective removal of oxophenylacetyl ester in saccharides' by Javeed Ur Rasool et al., Org. Biomol. Chem., 2021, 19, 338–347, DOI: ; 10.1039/d0ob02192j .